Crash of Imperial Russian Train on October 17, 1888, in German Press of Late 19th Century - N. A. Vlasov (Научный диалог)
This study aims to explore the distinctive features of how Russian events were portrayed in the German press of the late 19th century, focusing on publications concerning the crash of the imperial train near the Borki station in October 1888. It examines the influence of established images and stereotypes on the interpretation of information coming from Russia as presented in German newspapers. The primary sources include influential daily newspapers that significantly shaped public opinion in Germany. The findings suggest that, despite having access to accurate and detailed factual information about the imperial train crash in the Russian Empire, the German press interpreted these events through the lens of prevailing stereotypes: (1) the image of Alexander III as a noble yet reserved and distrustful individual; (2) the notion of a powerful pan-Slavic “war party” within the elite and society of the Russian Empire, countered by a peace-loving emperor; (3) perceptions of widespread corruption, deception, and incompetence among officials across all branches of government; and (4) the portrayal of Baltic Germans as the most loyal, honest, industrious, and professional subjects of the Russian emperor, whose removal from the administrative elite could lead to disastrous consequences for the state. It is noted that the evolving image of Russia in Germany had a significant impact on the development of Russian-German relations at the end of the 19th century.